PELAKSANAAN PROGRAM KETERAMPILAN MENJAHIT PADA REMAJA PUTUS SEKOLAH DI PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI PEKANBARU - Santy Restika Hutabarat Restika Hutabarat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study discusses the implementation of the program sewing skills in teenagers dropping out of school at the Young Children's Social Development (PSBR) Rumbai Pekanbaru. To determine the program implementation sewing skills then this review of resource materials, teaching methods, tools, and teaching and learning. The approach used in this study is a qualitative approach with descriptive methods. As a means of data collection used interview techniques, observation, interviews, documentation. Tool or instrumenya is the researchers themselves. As research subjects, namely Instructor Department Sewing, Sewing Skills Companion Programs and Citizens majors learn sewing skills. The research findings show that implementation of the program sewing skills conclusion that can be drawn from this study that the implementation of the program sewing skills in the Young Children's Social Development (PSBR) Rumbai Pekanbaru goes well, it meets the elements in the teaching and learning component that is a) lesson materials, b ) Learning Method, c) Tools, d) Teaching and learning activities. Keywords: Sewing Skills Program Implementation